Construction and Immunogenicity of a Recombinant Pseudorabies Virus Expressing SARS-CoV-2-S and SARS-CoV-2-N - Li, Ruoying; Shao, Guanming; Xie, Zi; Hu, Zezhong; Feng, Keyu; He, Jiahui; Wang, Hailong; Fu, Jun; Zhang, Xinheng; Xie, Qingmei (Frontiers in Veterinary Science, 2022)
Coronavirus (CoV) is an important pathogen of humans and animals, which can infect humans or animals through the respiratory mucosal route. Syndrome coronavirus 2 (SARS-CoV-2) is quite similar to syndrome coronavirus (SARS-CoV) with the same receptor, angiotensin-converting enzyme 2 (ACE2). The S and N proteins are the most important protective antigens of the SARS-CoV-2. The S protein on the viral membrane mediates the virus attachment with the host cells and the N protein is the most abundant in expression during infection. In this study, the recombinant viruses expressing the S and N proteins of SARS-CoV-2 were successfully constructed by Red/ET recombinant technology using Pseudorabies virus (PRV) vaccine strain Bartha-K61 as a viral vector. Genetic stability and growth kinetics analysis showed that the recombinant viruses rPRV-SARS-CoV-2-S and rPRV-SARS-CoV-2-N had similar genetic stability and proliferation characteristics to the parental PRV. The immunoassay results in mice showed that the two recombinant viruses could induce specific antibodies against S and N of SARS-CoV-2 in vivo. Therefore, PRV is feasible and promising as viral vectors to express SARS-CoV-2-S and SARS-CoV-2-N genes. This study can provide a reference for future research on live vector vaccines for domestic animals, pets and wild animals.